Application of Catalysts Derived from Renewable Resources in Production of Biodiesel - Kanokwan Ngaosuwan; Apiluck Eiad‐ua; Atthapon Srifa; Worapon Kiatkittipong; Weerinda Appamana; Doonyapong Wongsawaeng; Armando T. Quitain; Suttichai Assabumrungrat (My University, 2022)
Development of heterogeneous catalysts particularly those derived from renewable resources is an interesting research topic. Various renewable resources such as animals, plants, natural materials, and industrial wastes are valuable resources for production of catalysts, supports, and materials for different applications including biodiesel production. For example, animal- and natural-based resources contain metal oxides with base properties suitable for catalyzing transesterification, while plant and industrial wastes contain high carbonaceous materials, which could be used as a catalyst support for both esterification and transesterification. This chapter summarizes heterogeneous catalysts derived from different renewable resources for biodiesel production with particular focuses on their preparation methods, physicochemical properties, and catalytic activities for biodiesel production. In addition, the advantages, disadvantages, and challenges of these types of catalyst in the biodiesel production are addressed.
Keywords: Biodiesel Production and Applications; Catalysis and Hydrodesulfurization Studies; Enzyme Catalysis and Immobilization